2023
DOI: 10.7759/cureus.38135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hydroxyurea in Transfusion-Dependent Major β-Thalassemia Patients: A Meta-Analysis

Abstract: The present meta-analysis was conducted to determine the efficacy of hydroxyurea in patients with transfusion dependent major β-thalassemia. The present meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-analyses of Observational Studies in Epidemiology (MOOSE) guidelines. A systematic search was carried out to evaluate the efficacy of hydroxyurea in patients with transfusion-dependent B-thalassaemia using electronic databases, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In order to verify the possible impact of c4 in the development of therapeutic approaches for β-thalassemia, we examined the HbF inducing activity of c4 (a) in ErPCs from patients with different genotypes ( Figure 9 A) and (b) in comparison with inducers presently employed in clinical trials ( Figure 9 B). We selected hydroxyurea and rapamycin; hydroxyurea is employed in several clinical trials, such as NCT03183375 and NCT00809042 [ 38 , 39 , 40 , 41 , 42 , 43 ], while rapamycin (sirolimus) is employed in two clinical trials (NCT03877809 (A Personalized Medicine Approach for β-thalassemia Transfusion Dependent Patients: Testing sirolimus in a First Pilot Clinical Trial) and NCT04247750 (Treatment of β-thalassemia Patients with Rapamycin (Sirolimus): From Pre-clinical Research to a Clinical Trial) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to verify the possible impact of c4 in the development of therapeutic approaches for β-thalassemia, we examined the HbF inducing activity of c4 (a) in ErPCs from patients with different genotypes ( Figure 9 A) and (b) in comparison with inducers presently employed in clinical trials ( Figure 9 B). We selected hydroxyurea and rapamycin; hydroxyurea is employed in several clinical trials, such as NCT03183375 and NCT00809042 [ 38 , 39 , 40 , 41 , 42 , 43 ], while rapamycin (sirolimus) is employed in two clinical trials (NCT03877809 (A Personalized Medicine Approach for β-thalassemia Transfusion Dependent Patients: Testing sirolimus in a First Pilot Clinical Trial) and NCT04247750 (Treatment of β-thalassemia Patients with Rapamycin (Sirolimus): From Pre-clinical Research to a Clinical Trial) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, hydroxyurea (HU) is the only one approved drug able to induce fetal hemoglobin [ 14 , 18 , 38 , 39 , 40 , 41 ]. However, the side effects (as leukopenia and neutropenia) of the HU treatment, and the fact that it is active only in some patients, attracts limited enthusiasm for the use of this molecule [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is a need for an alternative treatment capable of alleviating symptoms associated with transfusion dependence and therefore iron overload [25]. HU and thalidomide, identified as potent Hb inducers, have been subjected to numerous trials, all of which have demonstrated their effectiveness in increasing Hb levels and reducing transfusion requirements in patients with TDT, whether administered individually or in combination [17,[23][24][25][26][27]. Our findings align with the aforementioned studies, as we observed an overall response rate of 90.1% to treatment (12.9% with HU alone, 0.8% with thalidomide alone, and 86.4% with the combination).…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61] Pharmacologic Therapies in Beta Hemoglobinopathies: Fetal Globin Gene Induction in the First Molecular Diseases In some subjects with β-thalassemia intermedia, HU increases HbF, reduces ineffective erythropoiesis, and reduces anemia and marrow fibrosis. [73][74][75][76] In a few patients with thalassemia intermedia treated with low doses of ≤10 mg/kg per day, four days per week, HU increased total Hb levels by preferentially increasing β-globin biosynthesis. 77 Interestingly, the presence of the Xmn-I T/T genotype or the BCL11A rs766432 C allele correlates strongly with response to HU (p <0.001), allowing for targeted selection of patients who are most likely to benefit.…”
Section: Hydroxyureamentioning
confidence: 99%